2001
DOI: 10.3109/00207450108986524
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Eeg Patterns in Treatment-Resistant Schizophrenic Patients

Abstract: This study was conducted in order to compare the EEG patterns of schizophrenics who do not respond to typical neuroleptics with those who do respond under typical neuroleptic medication and a group of controls. Absolute (AP) and relative power (RP), and inter- and intrahemispheric correlations were calculated. Nonresistant schizophrenics showed lower delta RP, higher alpha 1 AP and RP and higher correlation between prefrontal areas than the resistant ones and controls. Resistant schizophrenics showed lower alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…For example, Molina et al 33 reported that clozapine treatment was associated with increased occipital metabolism, including primary and association visual cortex, and additionally, that changes in positive symptoms correlated with increased activity in visual regions. In addition, Ramos et al 34 reported that treatment-resistant patients with schizophrenia had abnormal electroencephalographic (EEG) patterns in the occipital region. The purported mechanism through which the occipital gray matter could play a role in treatment response was not addressed in the present study, but animal data indicate that administration of antipsychotics is associated with D2 upregulation in all the major brain lobules, including the occipital lobe 35 as well as an increase in nerve growth factor in the occipital cortex.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Molina et al 33 reported that clozapine treatment was associated with increased occipital metabolism, including primary and association visual cortex, and additionally, that changes in positive symptoms correlated with increased activity in visual regions. In addition, Ramos et al 34 reported that treatment-resistant patients with schizophrenia had abnormal electroencephalographic (EEG) patterns in the occipital region. The purported mechanism through which the occipital gray matter could play a role in treatment response was not addressed in the present study, but animal data indicate that administration of antipsychotics is associated with D2 upregulation in all the major brain lobules, including the occipital lobe 35 as well as an increase in nerve growth factor in the occipital cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, goodR showed higher values of alpha1 since the pretreatment session that could be related to a better brain functional state that allowed them to respond to OLZ. This interpretation could be supported by previous results that showed that nonrefractory had higher alpha1 values than refractory schizophrenics under typical neuroleptics (Ramos et al, 2001a). On the other hand, Miyauchi et al (1990) have reported an increase of beta activity in nonmedicated schizophrenics that has been interpreted as an evidence of cortical excitability and Kemali et al (1992) found a reduction of fast beta after 28 days of treatment with haloperidol.…”
Section: Intrahemispheric Correlationmentioning
confidence: 53%
“…On the other hand, a different brain electrical activity (EEG) pattern was observed in TRS patients in comparison to good responders (Ramos et al, 2001a) and in an emotional recognition task, TRS showed higher deficits than good responders correlated with neuroleptic doses (Ramos et al, 2001b).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations